Presentation of menopausal symptoms: A village based community study - Srivastava, Mona; Srivastava, Ritu; Pandit, Balram (Asian Journal of Medical Sciences, 2014)
Background: The present observational, cross sectional study was carried out in rural women (n=117) from the Varanasi area with natural menopause to evaluate menopausal symptoms in women above the age of 40, as well as to evaluate the correlation of age on these symptoms. Materials and Methods: A crossectional assessment by interviewing regarding the menopausal complaints in the following 40-44(n=27), 45- 50(n=30) and above 50 (n =60) years age groups. Menstrual rating scale (MRS) was administered to all the women forming the sample. Results: Mean age at menopause was 47.35 years. Mean number of menopausal symptoms in three age groups were as (mean±SD)10.53±7.33, 7.70± 6.76 and14.50±10.77 respectively, which varied significantly (F=4.86, df=2, 87, P=0.009). The study reveal, varying nature of symptoms with age and MDSM (Mean Duration since Menopause), with vasomotor symptoms being more prevalent with lesser MDSM and psychological and rheumatic complaints more prevalent with increasing age and MDSM in this region. Conclusion: Such regional studies will help to corroborate data so that health care providers can plan strategies for the middle aged women suffering from these menopausal symptoms. DOI: http://dx.doi.org/10.3126/ajms.v6i1.8431 Asian Journal of Medical Sciences Vol.6(1) 2015 87-90